2015
DOI: 10.1667/rr13828.1
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism in a Matched Model of Radiation Resistance for Head and Neck Squamous Cell Cancer

Abstract: While radiation therapy is commonly used for treating cancer, radiation resistance can limit long-term control of the disease. In this study, we investigated the reprogramming of the energy metabolism in radiosensitive and radioresistant head and neck squamous cell carcinomas (HNSCC) using a preclinical matched model of radiation resistance. Our investigation found that radioresistant rSCC-61 cells: 1. They display increased glucose uptake and decreased fatty acid uptake; 2. They deviate from the classical War… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
101
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 51 publications
15
101
2
Order By: Relevance
“…Redox metabolism has been known for many decades as a key mediator of the response to radiation treatment with radiation resistant cells and tumors being characterized, in general, by a pattern of low basal ROS and upregulated antioxidant systems, consistent with our findings in HNSCC (10,11).…”
Section: Introductionsupporting
confidence: 90%
“…Redox metabolism has been known for many decades as a key mediator of the response to radiation treatment with radiation resistant cells and tumors being characterized, in general, by a pattern of low basal ROS and upregulated antioxidant systems, consistent with our findings in HNSCC (10,11).…”
Section: Introductionsupporting
confidence: 90%
“…Besides taxanes, NP formulations of orlistat may be used in combination with other chemotherapy classes, as inhibition of FASN can sensitize pancreatic or breast cancer cells to gemcitabine or 5-fluorouracil (57,58). NP formulations of orlistat may also be used with radiation, as others have shown that inhibition of FASN can sensitize head and neck squamous or prostate cancer cells to radiation (59,60). Given the strong synergy between NanoOrl and taxanes in taxane-resistant prostate cancer cells, our data warrant the further evaluation of NanoOrl for cancer therapy either alone or in combination with taxanes.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein (150 g) for each sample were loaded in 96-well plates along with kit standards. Sample absorbance was measured at 450 nm, and the NADPH/NADP ratio was determined according to kit protocol (40).…”
Section: Measurement Of Protein Carbonyl Levels and Lipidmentioning
confidence: 99%